The output effects of tax changes: Narrative evidence from Spain - Paula Gil; Francisco Martí; Richard Morris; Javier J. Pérez; Roberto Ramos (SERIEs - Journal of the Spanish Economic Association, 2019)
This paper analyses the level of inequality in Spain and how it evolved over the course of the past crisis and the early stages of the current recovery. To this end, it first introduces the various dimensions of wage, income, consumption and wealth inequality, and studies how they have developed. The analysis shows less wage dispersion in Spain than in other comparable economies, even after the crisis years, while the surge in unemployment during the period resulted in a high level of inequality in per capita income. The level of inequality in Spain is more moderate when total gross household income is analysed, decreasing during the crisis as a result of pensions developing more favourably than other sources of income, in conjunction with young people delaying setting up home. Inequality in per capita consumption rose during the crisis, particularly as a result of a decrease in expenditure on consumer durables by low-income households. Wealth inequality exceeds income inequality and increased during the downturn as a result of financial assets outperforming real assets. Nevertheless, Spain's wealth inequality is moderate by international standards, as ownership of real assets is more widespread than in other countries. The way inequality has evolved during the early stages of the current economic recovery shows that falling unemployment has enabled a reduction in wage income inequality, as well as in per capita income inequality, albeit to a lesser extent.
Keywords: E32; E62; H20; 330; Tax shocks; Narrative record; Fiscal policy; GDP growth